1995
DOI: 10.1029/95gl02409
|View full text |Cite
|
Sign up to set email alerts
|

Observation of electromagnetic oxygen cyclotron waves in a flickering aurora

Abstract: Instruments on the Auroral Turbulence rocket detected several intervals of weak electromagnetic oscillations at frequencies of 6-13 Hz in a strongly flickering auroral arc. These oscillations have amplitudes of up to 5B • 3 nT and 5E • 4 mV/m and have downward field-aligned Poynting fluxes of up to • 10 -s W/m 2. Fluctuations in the parallel electron flux at about 9 Hz were observed in association with the strongest of these oscillations. Simultaneous groundbased optical data show that the arc was flickering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 13 publications
8
34
0
Order By: Relevance
“…This frequency range is consistent with the O + ion cyclotron frequency at altitudes of several thousand kilometers. Such source altitudes are supported by various sounding rocket observations of precipitating particles: energy dispersion [McFadden et al, 1987], pitch angle dispersion [Temerin et al, 1993], and propagation delay of the waves with respect to the particles [Lund et al, 1995]. These observations support the idea that electromagnetic ion cyclotron (EMIC) waves cause the flickering aurora.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…This frequency range is consistent with the O + ion cyclotron frequency at altitudes of several thousand kilometers. Such source altitudes are supported by various sounding rocket observations of precipitating particles: energy dispersion [McFadden et al, 1987], pitch angle dispersion [Temerin et al, 1993], and propagation delay of the waves with respect to the particles [Lund et al, 1995]. These observations support the idea that electromagnetic ion cyclotron (EMIC) waves cause the flickering aurora.…”
Section: Introductionsupporting
confidence: 60%
“…McFadden et al [1998] reported the existence of oscillation in FABs around the H + ion cyclotron frequency by the FAST satellite measurements. Lund et al [1995] conducted ground-based optical observations in conjunction with wave and particle measurements on a sounding rocket platform launched into a flickering auroral arc. They reported electromagnetic fluctuations with modulated field-aligned electron fluxes at frequencies close to the O + ion cyclotron frequency in the auroral acceleration region.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, McFadden et al [1987], also using the velocity dispersion of the flux oscillations, placed the altitude between 4000 and 8000 km. Lund et al [1995] found the presence of electromagnetic oxygen cyclotron waves during the period of intense flux oscillations, and the lag time of the wave behind the electrons placed the altitude of the modulation In this paper we present ground based high speed photometric data of flickering aurora. The data were acquired to investigate the frequency distribution of flickering aurora without the 15 Hz Nyquist frequency limitation inherent in normal TV imagers recording at 30 frames per second.…”
Section: Introductionmentioning
confidence: 99%
“…Sounding rocket observations show that the flicker is produced by fluctuations in the field aligned electron flux, [Evans 1967;Arnoldy 1970;McFadden et al 1987;Lund et al 1995]. Based on the dispersion between the 16 and 60 keV channels, Evans [1967] found the fluctuations were generated near the rocket or, at the most, 1200 km from the rocket.…”
Section: Introductionmentioning
confidence: 99%
“…McHarg et al, 1998;Sakanoi and Fukunishi, 2004]. Typical observations are energy dispersed field aligned bursts of electrons in a wide range of energies from a few tens of eV up to the inverted-V potential of a few keV, sometimes co-occurring with weak electromagnetic oscillations at similar frequencies [Lund et al, 1995]. When this temporally varying precipitation enters the ionosphere it causes excitation and ionization with different temporal response at different altitudes [Peticolas and Lummerzheim, 2000].…”
Section: Introductionmentioning
confidence: 99%